Academic Advisor Support and Student Learning Experiences as Predictors of Deep Learning Pillars in Indonesian Higher Education - Evi Rahmiyati; Asmaul Husna; Achmad Mustofa; Muhammad Buchori Ibrahim (AL-ISHLAH: Jurnal Pendidikan, 2026)
Social support from academic advisors plays a crucial role in enhancing students’ learning experiences, particularly within a deep learning framework that emphasizes understanding, application, and reflection. This study aims to examine the relationship between academic advisor support and student learning experience in higher education. A quantitative correlational design was employed involving 386 students from 12 faculties at Universitas Syiah Kuala. The research instrument underwent expert judgment and item validity testing prior to data collection. Data were analyzed using Pearson correlation to examine relationships between variables and Chi-square tests to assess associations between meeting frequency and learning experience. The findings revealed a significant positive relationship between academic advisor support and student learning experience (r = 0.732, p 0.01). All three dimensions of deep learning—understanding, applying, and reflecting—demonstrated strong and significant correlations. Additionally, the Chi-square analysis indicated that higher frequency and intensity of meetings with academic advisors were significantly associated with improved learning experiences (p = 0.015). These results underscore the importance of academic advisors’ roles beyond administrative functions, highlighting their contribution to students’ academic engagement as well as cognitive and affective development. Effective advisor support fosters meaningful learning experiences aligned with deep learning principles. Future research should explore additional contextual factors influencing advisor–student interactions and extend the analysis across diverse institutional settings.